Religious tolerance in Malaysia: idealism and practice - Nazneen Ismail,; Aemy Elyani Mat Zain,; Haslina Ibrahim,; Safinah Ismail,; Nur Aisyah Abu Hassan,; Fatin Farzana Dass Meral, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Malaysia, as a pluralistic nation with a rich historical background, is recognized globally for its ability to maintain religious harmony. This study explores the factors contributing to religious tolerance in Malaysia, the challenges faced by religious communities and strategies to sustain societal stability. Key factors promoting tolerance include the wisdom of leaders, education, social and cultural traditions, the role of religious leaders, and personal experiences. However, challenges persist, such as ignorance, misuse of social media, emotional and political influences, differing educational backgrounds, and variations in religious practices. To address these issues, the study recommends fostering mutual respect among faiths, enhancing education focused on ethical interfaith interactions, disseminating accurate religious information, and enforcing laws that protect community rights while curbing misconduct. A collaborative, balanced approach involving education and enforcement is crucial. Leaders and religious figures play a pivotal role in ensuring that interfaith relations are rooted in knowledge, ethics, and cultural values, aligning with the nation’s aspiration for harmony amidst diversity.